2021
DOI: 10.2166/h2oj.2021.102
|View full text |Cite
|
Sign up to set email alerts
|

Application of fiber optics in water distribution networks for leak detection and localization: a mixed methodology-based review

Abstract: This study reviews the state-of-the-art application of fiber optics in water distribution networks for leak detection and localization. The use of fiber optics in the oil and gas sector has been well-established; however, its potential in water pipelines is not evident owing to limited research. This study, therefore, presents the research developments of fiber optics in water leak detection and localization using the mixed methodology approach by integrating bibliometric and systematic analyses. A scientometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…Detailed application of such techniques can be found in existing reviews (Chan et al, 2019; El‐Zahab & Zayed, 2019). It is pertinent to mention that new technologies like micro‐electromagnetic systems (MEMS)‐based customized sensors (Xu et al, 2019), fiber‐optic‐based sensors (Ibrahim et al, 2021), wireless sensing networks (WSNs) (See et al, 2009), internet of things (IoT) (Alves Coelho et al, 2020), and satellite imagery (Chen et al, 2020) for more precise and cost‐effective leak detection are being developed. Recently, Tariq et al (2021) present a detailed review covering the application of MEMS‐based accelerometers and wireless sensor networks.…”
Section: Current Technologies For Leak Detection and Localizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Detailed application of such techniques can be found in existing reviews (Chan et al, 2019; El‐Zahab & Zayed, 2019). It is pertinent to mention that new technologies like micro‐electromagnetic systems (MEMS)‐based customized sensors (Xu et al, 2019), fiber‐optic‐based sensors (Ibrahim et al, 2021), wireless sensing networks (WSNs) (See et al, 2009), internet of things (IoT) (Alves Coelho et al, 2020), and satellite imagery (Chen et al, 2020) for more precise and cost‐effective leak detection are being developed. Recently, Tariq et al (2021) present a detailed review covering the application of MEMS‐based accelerometers and wireless sensor networks.…”
Section: Current Technologies For Leak Detection and Localizationmentioning
confidence: 99%
“…(Iwanaga et al, 2022) Fiber optic sensors Uses a fiber optic-based reflective material for leak detection. (Ibrahim et al, 2021) are being explored by developing customized sensors based on novel technologies and demonstrating their acceptable capabilities against commercial sensors. For example, Xu et al ( 2019) demonstrated a small-sized MEMS-based hydrophone as a cost-effective solution for leak detection.…”
Section: Leak Noise Correlatorsmentioning
confidence: 99%
“…Research is focusing on developing non-invasive prognostic solutions rather than a posteriori diagnostic ones, thus identifying hydraulic leaks as early as possible while concurrently preventing severe network deterioration. For instance, optical fibers are unrolled along pipelines or coiled around pipes to locally detect water leaks as result of a change in the temperature or the dielectric properties of the fiber [ 12 , 13 ]. Electrical conductors can be drawn as well along pipes to perform time-domain reflectometry [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, extensive research has been conducted over the years, concerning the development of effective leak detection and localization methods [1][2][3][4]. These methods can rely on several physical phenomena from different areas, like optics [5][6][7][8][9], thermodynamics [10][11][12][13][14], acoustics [15][16][17][18][19][20][21][22][23][24][25][26], etc.…”
Section: Introductionmentioning
confidence: 99%